2015
DOI: 10.1039/c5cc00870k
|View full text |Cite
|
Sign up to set email alerts
|

Unprecedented formation of η4-(vinylketene)iron complexes from η4-(diene)iron complexes and aromatic compounds in the presence of a Lewis acid

Abstract: A novel and unprecedented formation of η(4)-(vinylketene)iron complexes from η(4)-(diene)iron complexes is described herein. Treatment of η(4)-(diene)iron complexes with a Lewis acid such as GaCl3 or AlCl3 in the presence of aromatic compounds under a CO atmosphere affords η(4)-(vinylketene)iron complexes via electrophilic aromatic substitution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…3 The preparation of these iron complexes has been achieved by different methods, including insertion into cyclopropene substrates, 4 and carbonylation of η 3 -carbenes, 5 η 4 -vinylketones, 6 η 2 -vinylketones 7 and η 4 -diene complexes, the last one being promoted by Lewis acids (Scheme 1). 8 These preparative methods have allowed the isolation and characterization of numerous η 4 -(vinylketene)iron(0) complexes as air-stable crystalline solids. The relative abundance of these complexes has also allowed their use in both mechanistic and reactivity studies, providing many analogues not only as intermediates proposed for the Dötz annulation 3 but also as unusual organometallic complexes or useful organic fragments.…”
Section: Introductionmentioning
confidence: 99%
“…3 The preparation of these iron complexes has been achieved by different methods, including insertion into cyclopropene substrates, 4 and carbonylation of η 3 -carbenes, 5 η 4 -vinylketones, 6 η 2 -vinylketones 7 and η 4 -diene complexes, the last one being promoted by Lewis acids (Scheme 1). 8 These preparative methods have allowed the isolation and characterization of numerous η 4 -(vinylketene)iron(0) complexes as air-stable crystalline solids. The relative abundance of these complexes has also allowed their use in both mechanistic and reactivity studies, providing many analogues not only as intermediates proposed for the Dötz annulation 3 but also as unusual organometallic complexes or useful organic fragments.…”
Section: Introductionmentioning
confidence: 99%
“…η 4 -(1,3-Diene)iron complexes are common in organometallic chemistry, and particularly in organic synthesis, , owing to their high availability, thermal stability, and low toxicity. As part of our continuing interest in the chemistry of the organoiron compounds, we recently reported that treatment of η 4 -(1,3-diene)iron complexes with Lewis acid in the presence of an aromatic compound under a carbon monoxide (CO) atmosphere produced η 4 -(vinylketene)iron complexes . Additionally, the iron complexes of vinylketenes exhibit noteworthy synthetic transformations. , For example, electron-deficient alkynes add to the vinylketene complexes via insertion to yield stable 1:1 adducts (eq ).…”
mentioning
confidence: 99%
“…(Vinylketenimine)iron complex 1a was prepared from a η 4 -(vinylketene)iron complex and diethyl N -octylphosphoramidate, and subsequently treated with diethyl acetylenedicarboxylate (2.0 equiv) in toluene (eq ), to yield a yellow oil. Infrared and NMR spectral analysis indicated that this oil lacked the carbonyl absorptions of the expected iron complex 3a , but instead contained two ethoxycarbonyl groups ( 2a ).…”
mentioning
confidence: 99%
See 1 more Smart Citation